India-United States Strategic Relations: China as a Factor - Mohammad Samir Hussain (Journal of Political Studies, 2012)
The constructive relationship between India and the United States that witnessed significant upward trajectory by the dawn of the twenty-first century is being portrayed by many in India and abroad as moving in the direction of containing China. Their perception is based on the fact that India and the United States enjoy more convergences of interests than the divergences of interests. The paper argues that containment of China would result to serious strategic and economic implications for India. It should be in the interest of India and the United States that they encourage China rise in positive direction that doesn’t pose any threat to both of them rather than in a negative one. This way they can receive maximum benefit out of the expanding relations, both economically and militarily. It further argues that the changing international security environment requires cooperation between these three countries rather than confronting each other.